Cyclovirobuxine D, a cardiovascular drug from traditional Chinese medicine, alleviates inflammatory and neuropathic pain mainly via inhibition of voltage-gated Cav3.2 channels - Su, Deyuan; Gong, Ye; Li, Songyu; Yang, Jian; Nian, Yin (Frontiers in Pharmacology, 2022)
Cyclovirobuxine D (CVB-D), the main active constituent of traditional Chinese medicine Buxus microphylla, was developed as a safe and effective cardiovascular drug in China. B. microphylla has also been used to relieve various pain symptoms for centuries. In this study, we examined and uncovered strong and persistent analgesic effects of cyclovirobuxine D against several mouse models of pain, including carrageenan- and CFA-induced inflammatory pain and paclitaxel-mediated neuropathic hypersensitivity. Cyclovirobuxine D shows comparable analgesic effects by intraplantar or intraperitoneal administration. Cyclovirobuxine D potently inhibits voltage-gated Cav2.2 and Cav3.2 channels but has negligible effects on a diverse group of nociceptive ion channels distributed in primary afferent neurons, including Nav1.7, Nav1.8, TRPV1, TPRA1, TRPM8, ASIC3, P2X2 and P2X4. Moreover, inhibition of Cav3.2, rather than Cav2.2, plays a dominant role in attenuating the excitability of isolated dorsal root ganglion neurons and pain relieving effects of cyclovirobuxine D. Our work reveals that a currently in-use cardiovascular drug has strong analgesic effects mainly via blockade of Cav3.2 and provides a compelling rationale and foundation for conducting clinical studies to repurpose cyclovirobuxine D in pain management.